554. Does Protease Inhibitor (PI) Monotherapy Select Primary PI Resistance?. (26th November 2018) - Saling, Christopher; Atallah, Liana; Haddad, Tyler; Learned, Brooke; Slim, Jihad
Abstract: Background: Combination drug therapy is the standard of care for HIV treatment. PI monotherapy is considered experimental in the United States. However, some patients end up receiving PI monotherapy secondary to resistance and/or drug intolerance to other antiretroviral (cART) classes. This study will discuss real-life clinical results in patients on PI monotherapy and examine the potential for the development of primary PI mutations. Methods: An observational retrospective study conducted in an inner-city HIV clinic identified 10 patients on PI monotherapy who each had two GenoSure Archive® (Labcorp) resistance profiles performed. Gender, race, prior cART, and baseline VL and CD4+ count were captured. VL and CD4+ count were trended in the time period between resistance tests. These profiles were then compared checking for the emergence of new primary PI mutations. Results: Seven out of 10 patients were African American, two were Hispanic, one was Caucasian, and half were male. The mean time interval between archived resistance tests was 6.87 months. During the time between resistance profiles, nine were on darunavir and one switched from lopinavir to darunavir for less pill burden. Eight had an undetectable VL (defined by <50 copies/mL) at the first resistance test, seven had undetectable VL at the second resistance test, and six remained undetectable over the entire period between profiles. There were three that demonstrated blips in VL and one that experienced virological failure between the two sets of resistance tests. One patient had an initial resistance profile showing primary resistance to lopinavir. No patients gained any primary PI mutations to darunavir. Conclusion: The results of this study suggest that mainly darunavir-based PI monotherapy has good genetic barrier, even in the setting of virological failure. Larger studies examining similar data over longer durations are needed to confirm this finding. Disclosures: All authors: No reported disclosures.